2016
DOI: 10.3346/jkms.2016.31.12.1976
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Young Age at Diagnosis on Survival in Patients with Surgically Treated Renal Cell Carcinoma: a Multicenter Study

Abstract: The prognostic significance of age in renal cell carcinoma (RCC) is a subject of debate. The aim of the present multi-institutional study was to evaluate the impact of age on clinicopathological features and survival in a large cohort of patients with RCC. A total of 5,178 patients who underwent surgery for RCC at eight institutions in Korea between 1999 and 2011 were categorized into three groups according to age at diagnosis as follows: young age (< 40 years, n = 541), middle-age (≥ 40 and < 60 years, n = 2,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
33
0
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(38 citation statements)
references
References 32 publications
2
33
0
3
Order By: Relevance
“…Regarding clinical and pathological characteristics according to age, recent studies have indicated that older patients are more likely to have a poorer general condition and more aggressive pathological features than young patients . We also observed similar trends, with older patients having higher values for ECOG PS, T stage, and Fuhrman grade.…”
Section: Discussionsupporting
confidence: 81%
“…Regarding clinical and pathological characteristics according to age, recent studies have indicated that older patients are more likely to have a poorer general condition and more aggressive pathological features than young patients . We also observed similar trends, with older patients having higher values for ECOG PS, T stage, and Fuhrman grade.…”
Section: Discussionsupporting
confidence: 81%
“…Some studies reported that the 40 years old was suitable to act as the dividing line between young and old CCRCC patients. Xavier Taccoen But the result of the Kaplan-Meier analysis showed that the CCS rate was significantly better in the young age group than the other groups (middle age: ≥ 4 and < 60 years ; old age: ≥ 60 years) [10].…”
Section: Discussionmentioning
confidence: 99%
“…Most previous studies reported the role of age as a prognostic factor in RCC patients with all subtypes and all stages, telling conflicting conclusions [7,[11][12][13][14][15][16][17][18][19][20]. Of these studies, some have claimed that the prognosis of RCC in younger patients did not differ from that in older patients [13][14][15]. The most recent multicenter study including 5,178 patients who underwent surgery for RCC showed no significant difference in CSS among three age groups (< 40 years, ≥ 40 and < 60 years, ≥60 years) [15].…”
Section: Discussionmentioning
confidence: 99%
“…Of these studies, some have claimed that the prognosis of RCC in younger patients did not differ from that in older patients [13][14][15]. The most recent multicenter study including 5,178 patients who underwent surgery for RCC showed no significant difference in CSS among three age groups (< 40 years, ≥ 40 and < 60 years, ≥60 years) [15]. However, more studies reported better CSS rates in young RCC patients than in older ones [16][17][18][19][20].…”
Section: Discussionmentioning
confidence: 99%